GAMBARAN EFEKTIVITAS METODE UJI DALAM PENGUJIAN GETAH PELEPAH POHON PISANG KEPOK SEBAGAI ANTIBAKTERI PADA STAPHYLOCOCCUS AUREUS - Farhat, Rifa Nurafifah; Salman, Yuliana; Hidriya, Hajrah (Politeknik Unggulan Kalimantan, 2025)
Antibiotic resistance testing of bacteria has many different methods and techniques, namely the well diffusion method, the disc diffusion method, the cylinder diffusion method, the dilution method, and the dilution diffusion method. The many antibacterial examination methods available for bacteria make people consider a lot in determining the appropriate method. The purpose of this study was to determine the effectiveness of the test method in antibacterial testing on Staphylococcus aureus. This study was conducted using the disc diffusion method and the well diffusion method, using distilled water as a negative control, Ampicillin antibiotics as a positive control. This study used concentrations of 15%, 30% and 60% with three repetitions. The results of the difference in the average measurement of the inhibition zone of the kepok banana tree sap extract against Staphylococcus aureus bacteria were respectively 0 mm, 3.2 mm, 3.2 mm, 3 mm, and 2.5 mm. The results showed that the difference in the average diameter of the inhibition zone of the well diffusion method was greater than that of the disc diffusion method. It was concluded that the antibacterial test method using the well diffusion method was more effective than the disc diffusion method